Damage of testicular cell macromolecules and reproductive capacity of male rats following co-administration of ethambutol, rifampicin, isoniazid and pyrazinamide - Shayakhmetova, Ganna Mykhailivna (Slovak Toxicology Society SETOX, 2012)
The necessity to minimize adverse effects of tuberculosis chemotherapy requires a comprehensive evaluation of the effects of antituberculosis drugs on the reproductive system and testicular cell macromolecules. The epidemiological situation of tuberculosis in Central and Eastern Europe is getting worse. Data on adverse effects of antituberculosis drugs are scare concerning particularly their effects on the reproductive system. The aim of the present study was to investigate the potential effect of ethambutol, rifampicin, isoniazid and pyrazinamide co-administration on lipid peroxidation, glutathione content and protein SH-groups, DNA fragmentation levels, the reproductive capacity of Wistar male rats and the antenatal development of their posterity. The rats (150–170 g) were divided into two groups: group I – received antituberculosis drugs suspended in 1% starch gel per os: ethambutol – 155 mg/kg b.w./day, rifampicin – 74.4 mg/kg b.w./day, isoniazid – 62 mg/kg b.w./day, pyrazinamide – 217 mg/kg b.w./day, group II (control) – received only starch gel in corresponding volumes. The contents of TBA-active compounds, glutathione and protein SH-groups in testis and sperm were determined spectrophotometrically, the DNA-fragmentation was determined using an UV transilluminator (BIORAD, USA), reproductive system indices were measured by standard methods. The co-administration of therapeutic doses of ethambutol, isoniazid, rifampicin and pyrazinamide to male rats during the period of spermatogenesis caused an increase in the rate of thiobarbituric acid reactive substances formation in testis and sperm, decrease of testis glutathione and protein SH-group contents, significant changes in DNA fragmentation, fatal decrease of male fertilizing capacity and fertility, and increase of pre- and post-implantation embryo lethality. The changes in reproductive indices could be the result of direct or indirect effects of one or more drugs investigated.